Evaluating the phytotoxicity of sodium diclofenac treated with heterogeneous photocatalysis - J. T. dos Santos; L. B. G. A. Morselli; C. M. Pinheiro; V. L. Bobrowski; C. C. de Escobar; M. S. Quadro; R. Andreazza (International Journal of Environmental Science and Technology, 2026)
Pharmaceuticals are increasingly detected in surface water, and even at trace concentrations, they may pose ecological and health risks. In this study, heterogeneous photocatalysis using titanium dioxide (TiO 2 ) was applied under simulated solar irradiation to degrade sodium diclofenac. Irradiation times of 60, 120, and 180 min were used with a TiO 2 loading of 0.6 g L −1 . Under these conditions, only ~ 20% diclofenac degradation and 50% COD removal were achieved, indicating relatively low treatment efficiency. Cytotoxicity, genotoxicity, mutagenicity, and cytokinesis assays with Allium cepa did not reveal statistically significant toxic effects; however, some genotoxic responses were observed. Overall, no clear evidence of transformation products more harmful than the parent compound was detected, although this result should be interpreted with caution, given the observed genotoxic responses. Overall, heterogeneous photocatalysis exhibited limited performance under the tested conditions. Further studies with a broader experimental design and more detailed analytical approaches are required to confirm both its efficiency and safety.